The lighter side of mathematics - Eugene Strens Memorial Conference on Recreational Mathematics and its History (1986 : University of Calgary, Calgary); Guy, Richard K.; Woodrow, Robert E.; Mathematical Association of America (Washington, D.C. : MAA Pub., 1994)
41